Characterization of flavonoid and naphthopyranone derivatives from Eriocaulon ligulatum using liquid chromatography tandem mass spectrometry - Dos Santos, Lourdes Campaner [UNESP]; Da Silva, Marcelo Aparecido [UNESP]; Rodrigues, Clenilson Martins [UNESP]; Carbone, Virginia; Napolitano, Assunta; Bassarello, Carla; Mari, Angela; Piacente, Sonia; Pizza, Cosimo; Vilegas, Wagner [UNESP] (My University, 2009)
Liquid chromatography-electrospray ionization multistage ion trap mass spectrometry (LC-ESI-IT-MSn) was used to analyze the secondary metabolites in the methanol extract of the capitulae of Eriocaulon ligulatum. The major components were monoand diglycosides of flavonoids and naphthopyranones. Eleven compounds, including four new flavonol glycosides, were identified based on their fragmentation patterns in MS experiments and on NMR analysis of the isolated compounds. The described data may contribute to a better understanding of the taxonomic classification of the Eriocaulaceae family.
Keywords: Eriocaulon ligulatum; Flavonoids; LC/MS/MS; Naphthopyranones